Evaluation of Low Temperature Cracking of Asphalt Mixture Modified with PPA Using Acoustic Emission Technique - Kodadadi, Mojtaba; Khodaii, Ali (International Journal of Engineering and Technology, 2018)
In this study, the behavior of asphalt mixture was studied using non-destructive Acoustic Emission (AE) technique at low temperatures. For this purpose, two types of bitumen 60/70 and 85/100 with two types of limestone and Silica aggregate were used to construct asphalt mixtures. Polyphosphoric acid (PPA) was used to modify the bitumen in the dosage of 0, 0.5, 1.0 and 1.5% of bitumen weight. Semicircular bending test (SCB) under a steady increasing strain at a rate of 3mm/min was conducted at 0, -10-, and -20 Â°C. Two AE channels were used to record the Sinusoid output around the crack of SCB sample during crack growth. Analysis of the results obtained from this study using SPSS software indicates that there is a significant relationship between the failure energy of SCB samples and the number of impacts received from AEs. Furthermore, AE energy has a good agreement with the sample failure energy. According to the failure criterion, asphalt mixtures containing 85/100 bitumen modified by 1.0% of PPA and limestone aggregate exhibit more crack resistance among other compositions.Â Â